2021
DOI: 10.5946/ce.2020.275
|View full text |Cite
|
Sign up to set email alerts
|

Insufflation of Carbon Dioxide versus Air During Colonoscopy Among Pediatric Patients: A Systematic Review and Meta-Analysis of Randomized Controlled Trials

Abstract: Background/Aims: Carbon dioxide is increasingly used in insufflation during colonoscopy in adult patients; however, air insufflation remains the primary practice among pediatric gastroenterologists. This systematic review and meta-analysis aims to evaluate insufflation using CO 2 versus air in colonoscopies in pediatric patients. Methods: Individualized search strategies were performed using MEDLINE, Cochrane Library, EMBASE, and LILACS databases following Preferred Reporting Items for Systematic Reviews and M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…In one ( 6 ), pain reduction was only evident following adjusting for baseline abdominal pain, and no such benefit was observed in another ( 8 ). A recent meta-analysis concluded that there is limited evidence to recommend routine use of CO 2 in pediatric endoscopy ( 12 ), while another concluded that CO 2 gas is preferred for pediatric colonoscopy ( 13 ). Furthermore, peak end-tidal CO 2 (EtCO 2 ) measurement in 2 of the pediatric studies showed higher EtCO 2 in the CO 2 group, raising concerns about systemic absorption of CO 2 ( 6 , 8 ).…”
mentioning
confidence: 99%
“…In one ( 6 ), pain reduction was only evident following adjusting for baseline abdominal pain, and no such benefit was observed in another ( 8 ). A recent meta-analysis concluded that there is limited evidence to recommend routine use of CO 2 in pediatric endoscopy ( 12 ), while another concluded that CO 2 gas is preferred for pediatric colonoscopy ( 13 ). Furthermore, peak end-tidal CO 2 (EtCO 2 ) measurement in 2 of the pediatric studies showed higher EtCO 2 in the CO 2 group, raising concerns about systemic absorption of CO 2 ( 6 , 8 ).…”
mentioning
confidence: 99%